From neglect to earlier diagnosis: a qualitative meta-synthesis of psycho-social factors associated with consultation delay in advanced basal cell carcinoma. Issue 8 (14th September 2022) - Legrand, A.; Quintard, B.; Garrouteigt, C.; Beylot-Barry, M.; Broc, G.
ABSTRACT: Local malignant potential of basal cell carcinoma (BCC) can lead at advanced stages to the destruction of underlying tissues and significant morbidity. The primary risk factor for progression of advanced basal cell carcinoma (aBCC) is the long duration of the tumour, which results from delay in seeking medical care. To assess the implication of psycho-social factors in the delay before the first medical consultation among patients with aBCC, in order to identify potentially targetable factors enabling earlier diagnosis. Three-step qualitative meta-synthesis: (1) systematic review of the literature; (2) structured qualitative analysis of these documents; (3) construction of a logical model. After screening, 81 articles were included. Self-neglect and denial in patients are roundly put forward as the main obstacles to consultation. We found that avoidance behaviour, mistaken interpretation and banalisation of symptoms, and fear of treatment all played a role. The strongest motivation to seek help comes from the realisation that new symptoms may be dangerous; the role of interpersonal surroundings is highlighted as helpful. Patient delay has multifactorial origins in aBCC, especially self-neglect ranging from denial of tumours to conscious refusal of treatment.